ANALYSIS OF THE PERSONNEL POTENTIAL EFFICIENCY OF THE PHARMACEUTICAL INSTITUTION - Марина Юрьевна Клищенко; Дмитрий Анатольевич Кузнецов (Медицина в Кузбассе)
Objective – to analyse the personnel management system of the pharmaceutical institution.